Morphology improvement of SiC trench by inductively coupled plasma etching using Ni/Al2O3 bilayer mask. (15th August 2017) - Li, Jingjie; Cheng, Xinhong; Wang, Qian; Zheng, Li; Shen, Lingyan; Li, Xinchang; Zhang, Dongliang; Zhu, Hongyue; Shen, DaShen; Yu, Yuehui
Abstract: In this work, we performed an inductively coupled plasma (ICP) etching of SiC substrates using different masks including SiO2, Ni, Ni/SiO2 and Ni/Al2 O3, and the properties of trenches were systemically analyzed. In comparison with other three masks, Ni/Al2 O3 mask prevented contamination of F or Ni element from diffusion into SiC, and achieved the optimized trench morphology with a surface roughness of 0.2 nm, steep sidewall and no micro-trench at the corner. Al2 O3 dielectric films were deposited on trenches by plasma enhanced atomic layer deposition (PEALD), and its critical breakdown electrical field was much higher with Ni/Al2 O3 mask, which could reach 7.7 MV/cm. So it was believed that Ni/Al2 O3 mask ensured the formation of SiC trench with superior morphology.